Sulfite determination in young coconut beverage using iodemetric titration method - Lopez, Crisanto Maglaque; Luna, Myrna Benita Z. (2002., 2002)
ABSTRACT The study aimed to evaluate the use of iodometric titration method in determining sulfite in young coconut beverage. Accuracy, precision, limit of reliable measurement and specificity of the method were measured by conducting a recovery test. It was established that the method can accurately and precisely measure sulfite in the beverage at concentrations ≥ 50 ppm giving a recovery of > 80% and CV of ≤ 10%. The limit of reliable measurement of the iodometric titration method for young coconut beverage is 50 ppm. Recoveries of spiked sulfite in various sample matrices including blank, pure liquid endosperm and formulated young coconut beverage samples were not significant (p > 0.05). Sulfite in 25 samples of commercial ready-to-drink young coconut beverage collected from the National Capital Region and Laguna was quantified using the evaluated iodometric titration method. Sulfite levels in these samples ranged from 3.34 ± 1.89 to 20.53 ± 6.87 ppm. Deliberate or incidental incorporation through sulfite-contaminated ingredients were cited as possible reasons for the presence of sulfite in the beverage
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beverages; Coconut products